Influence and Linkage of Buyers’-Suppliers’ Attitude Towards E-Procurement Adoption in Developing Countries: Tanzania Context (International Journal of Applied Research in Management and Economics, 2020)
The objective of this study was to fill the knowledge gap through analyzing the influence and linkage of buyers’-suppliers’ attitude towards e-procurement adoption in developing countries, Tanzania in particular. This study was guided by Unified Theory of Acceptance and Use of Technology and the Technology, Organization and Environment model. The study adopted cross-sectional survey research design. The study also used non-probability (purposive) sampling and probability (stratified) sampling techniques. Sample size was 157. Questionnaires and documentary review were used for data collection. The collected data were analysed by using Partial Least Squares Structural Equation Modelling with the help of SmartPLS 3 software. Findings reveal that buyers’-suppliers’ attitude has direct influence and links the performance expectancy, relative advantage and legal framework towards e-procurement adoption in public sector. The findings and recommendations of this study are anticipated to improve the adoption of e-procurement in developing countries, Tanzania in particular.